Seismic Damage State Limits of Non-Engineered Buildings Considering the Randomness of Ground Motions - Kristiawan, Stefanus Adi; Sangadji, Senot; Purwanto, Edy; Safarizki, Hendramawat Aski; Sulthon, Aufa Hanif Abiyyu; Muflih, Ahadin Banu (Institute of Research and Community Outreach - Petra Christian University, 2025)
Earthquake-resistant structures are vital to achieving sustainable buildings as they minimize damage during seismic events and allow for easier repairs. In contrast, non-engineered buildings (NEBs) often suffer severe damage, contributing to waste that burdens the environment. Many residential buildings in Indonesia fall into this NEB category, so evaluating the extent of damage during earthquakes is essential. This study analyzed the seismic response of NEB using Incremental Dynamic Analysis (IDA). The dynamic pushover curves derived from the IDA were further examined to identify the damage limit states pertinent to NEB, considering the randomness of the ground motions. The proposed damage limit states, categorized into various levels (DS1-DS4) and their corresponding uncertainties due to random ground motions, highlight the vulnerability of NEBs to seismic events. The high probability of damage to NEBs makes stakeholders aware of the need to take measures to improve the resilience and, ultimately, the sustainability of residential buildings.